FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI MAHASISWA MENGENAI ETIKA PENGGELAPAN PAJAK (Survei pada Mahasiswa Akuntansi Fakultas Ekonomi Perguruan Tinggi Swasta di Surakarta) - Fitria Anggrahini; Fadjar Harimurti; Dewi Saptantinah Puji Astuti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Tax evasion in Indonesia is still a lot, such as reporting smaller sales, inflating company costs at a fictionalized cost. The purpose of this research is to analyze the significance of the influence of taxation system, discrimination, technology and information on taxation and justice to the ethical perception of tax evasion in accounting students Faculty of Private college economics In Surakarta This research took samples of 118 respondents from 1,160 accounting students of the Faculty of Economics of Private universities in Surakarta who have been attending a tax practice course. Data collection methods used: questionnaires and documentation. Technical analysis of data used for validity tests, reliability tests, classical assumption tests, and multiple linear regression analyses. The results of the significance testing of the taxation system against tax evasion significantly negatively affect. Technology testing and taxation information negatively affect tax evasion, and the testing of the influence of justice gained significant negative results against tax evasion. As for discrimination, the results of significant positive effect on tax evasion are obtained.